Airborne pollen flora of a deciduous mesic forest in Turkey (Bangladesh Journal of Plant Taxonomy, 2010)
Airborne pollen composition of a deciduous mesic forest in northwestern Turkey is compared with the flora of the forest and a wider area. The airborne assemblage is constituted by 641.553 pollen belonging to 32 orders, 54 families and 96 genera. Of these, 380.000 (59.2%) belong to native and 257.180 (40.1%) to non-native plants. Among the native taxa arboreal pollen (AP) is represented by 55.7% and non-arboreal (NAP) by 44.3%. All of the arboreal elements of the forest are Quercus, Castanea, Carpinus, Ulmus, Alnus, Populus, Salix, Fagus, Tilia, Acer, Corylus, Prunus, Rubus, Ligustrum, Phillyrea which represented in the airborne assemblage. Incorporation of NAP to airborne composition is less than AP and they more likely provide an indication of the composition of local plant communities and hence represent vegetation of immediate vicinity. The most common NAP taxa are Poaceae, Plantaginaceae, Asteraceae, Urticaceae, Apiaceae, Cannabaceae, Polygonaceae and Cyperaceae. Pollen of climbers are less represented than AP but more than NAP taxa. Platanus orientalis (30.7%) and Pinus and Cupressus (20.2%) constitute half of the non-native flora; the rest is the pollen of exotic, alien and horticultural taxa from numerous parks and gardens in İstanbul.